Ethnobotanical Survey on Skin Whitening Prescriptions of Traditional Chinese Medicine in Taiwan - Ko, Chien-Yu; Chao, Jung; Chen, Pei-Yu; Su, Shan-Yu; Maeda, Tomoji; Lin, Chin-Yu; Chiang, Hung-Che; Huang, Shyh-Shyun (Frontiers in Pharmacology, 2021)
The increasing interest and demand for skin whitening products globally, particularly in Asia, have necessitated rapid advances in research on skin whitening products used in traditional Chinese medicine (TCM). Herein, we investigated 74 skin whitening prescriptions sold in TCM pharmacies in Taiwan. Commonly used medicinal materials were defined as those with a relative frequency of citation (RFC) >0.2 and their characteristics were evaluated. Correlation analysis of commonly used medicinal materials was carried out to identify the core component of the medicinal materials. Of the purchased 74 skin whitening prescriptions, 36 were oral prescriptions, 37 were external prescriptions, and one prescription could be used as an oral or external prescription. After analysis, 90 traditional Chinese medicinal materials were obtained. The Apiaceae (10%; 13%) and Leguminosae (9%; 11%) were the main sources of oral and external medicinal materials, respectively. Oral skin whitening prescriptions were found to be mostly warm (46%) and sweet (53%), while external skin whitening prescriptions included cold (43%) and bitter (29%) medicinal materials. Additionally, mainly tonifying and replenishing effects of the materials were noted. Pharmacological analysis indicated that these medicinal materials may promote wound healing, treat inflammatory skin diseases, or anti-hyperpigmentation. According to the Spearman correlation analysis on interactions among medicinal materials with an RFC>0.2 in the oral skin whitening prescriptions, Paeoniae radix alba and Atractylodis macrocephalae rhizoma showed the highest correlation (confidence score=0.93), followed by Jujubae fructus and Astragali radix (confidence score=0.91). Seven medicinal materials in external skin whitening prescriptions with an RFC >0.2, were classified as Taiwan qī bái sàn (an herbal preparation), including Angelicae dahuricae radix, Poria, Bletillae rhizoma, Atractylodis macrocephalae rhizoma, Ampelopsis radix, Paeoniae radix alba, and Bombyx batryticatus. Skin whitening prescriptions included multiple traditional Chinese medicinal materials. Despite the long history of use, there is a lack of studies concerning skin whitening products, possibly due to the complex composition of traditional Chinese medicine. Further studies are required to assess the efficacy and safety of these traditional Chinese medicinal materials for inclusion in effective, safe, and functional pharmacological products.